Association between Diet Quality and Frailty Prevalence in the Physicians' Health Study. Issue 4 (16th December 2019) - Ward, Rachel E.; Orkaby, Ariela R.; Chen, Jiaying; Hshieh, Tammy T.; Driver, Jane A.; Gaziano, J. Michael; Djousse, Luc
Abstract : OBJECTIVES: Limited data suggest that a healthy diet is associated with a lower risk of frailty. We sought to assess the relationship between three measures of diet quality and frailty among male physicians. DESIGN: Cross‐sectional analysis of a cohort study. SETTING: Physicians' Health Study. PARTICIPANTS: A total of 9861 initially healthy US men, aged 60 years or older, who provided data on frailty status and dietary habits. MEASUREMENTS: A cumulative deficit frailty index (FI) was calculated using 33 variables encompassing domains of comorbidity, functional status, mood, general health, social isolation, and change in weight. Diet quality was measured using the Alternative Healthy Eating Index (aHEI), Mediterranean Diet Score (MDS), and Dietary Approaches to Stop Hypertension (DASH). RESULTS: The FI identified 38% of physicians as non‐frail, 44% as pre‐frail, and 18% as frail. Multinomial logistic regression models adjusted for age, smoking status, and energy intake showed that compared with the lowest aHEI quintiles, those in the highest quintiles had lower odds of frailty and pre‐frailty compared with non‐frailty (odds ratio [OR] for frailty = .47; 95% confidence interval [CI] = .39‐.58; for pre‐frailty: OR = .75; CI = .65‐.87). Exercise did not modify this association ( P interaction >.1). Similar relationships were observed for DASH and MDS quintiles with frailty and pre‐frailty. Restricted cubic splines showed an inverse dose‐response relationship of diet quality scores with odds of frailty and pre‐frailty. CONCLUSION: Cross‐sectional data show an inverse dose‐response relationship of diet quality with pre‐frailty and frailty. Future longitudinal studies are needed to investigate whether healthier diet is a modifiable risk factor for frailty. ClinicalTrials.gov identifier: NCT00000500. J Am Geriatr Soc 68:770–776, 2020